Relative Histories Mediating History in Asian American Family Memoirs - Davis, Rocio G. (2022)
Relative Histories focuses on the Asian American memoir that specifically recounts the story of at least three generations of the same family. This form of auto/biography concentrates as much on other members of one's family as on oneself, generally collapses the boundaries conventionally established between biography and autobiography, and in many cases-as Rocío G. Davis proposes for the auto/biographies of ethnic writers-crosses the frontier into history, promoting collective memory. Davis centers on how Asian American family memoirs expand the limits and function of life writing by reclaiming history and promoting community cohesion. She argues that identity is shaped by not only the stories we have been told, but also the stories we tell, making these narratives important examples of the ways we remember our family's past and tell our community's story. In the context of auto/biographical writing or filmmaking that explores specific ethnic experiences of diaspora, assimilation, and integration, this work considers two important aspects: These texts re-imagine the past by creating a work that exists both in history and as a historical document, making the creative process a form of re-enactment of the past itself. Each chapter centers on a thematic concern germane to the Asian American experience: the narrative of twentieth-century Asian wars and revolutions, which has become the subtext of a significant number of Asian American family memoirs (Pang-Mei Natasha Chang's Bound Feet and Western Dress, May-lee and Winberg Chai's The Girl from Purple Mountain, K. Connie Kang's Home Was The Land of Morning Calm, Doung Van Mai Elliott's The Sacred Willow); family experiences of travel and displacement within Asia in the nineteenth and early twentieth centuries, which unveil a history of multiple diasporas that are often elided after families immigrate to the United States (Helie Lee's Still Life With Rice, Jael Silliman's Jewish Portraits, Indian Frames, Mira Kamdar's Motiba's Tattoos); and the development of Chinatowns as family spaces (Maxine Hong Kingston's China Men, Lisa See's On Gold Mountain, Bruce Edward Hall's Tea that Burns). The final chapter analyzes the discursive possibilities of the filmed family memoir ("family portrait documentary"), examining Lise Yasui's A Family Gathering, Ruth Ozeki Lounsbury's Halving the Bones, and Ann Marie Fleming's The Magical Life of Long Tack Sam. Davis concludes the work with a metaliterary engagement with the history of her own Asian diasporic family as she demonstrates the profound interconnection between forms of life writing.